Volumetric covering print-paths for additive manufacturing of 3D models. (July 2018) - Ezair, Ben; Fuhrmann, Saul; Elber, Gershon
Abstract: In additive manufacturing (AM), slicing is typically used to manufacture 3D models, one layer after another. Yet, in recent years quite a few hardware platforms were introduced toward the use of multi-axes AM with general 3D curves as print-paths. This paper presents algorithms for the generation of such general print-paths that can potentially be used to synthesize superior 3D models using AM. In slicing, a 3D model is decomposed into a series of parallel planar sections, which in turn are (usually) decomposed into a set of piecewise linear curves used as print-paths in the AM process. The methods we propose in this work ease this restriction, namely the print-paths are no longer limited to parallel planes. Like slicing, the methods we propose achieve a complete covering of a general volume with print-paths expressed as general curves. However, and unlike slicing, the created print-paths can conform better to the 3D model, its properties, and even user input. We expect that the added flexibility and freedom in the specification of AM print-paths, as opposed to limiting them to planar curves, will enable the synthesis of 3D models (using AM) with superior properties (such as mechanical strength and surface finish). As a proof of concept, we also present examples of 3D models manufactured with a low-end AM hardware and using the algorithms described in this paper. Highlights: Create covering curves for (possibly trimmed) trivariate volumes. Support covering curves for any 3D B-rep model with an external direction field. Enable the use of general (possibly user defined) 3D printing-paths.